Evektivitas Penggunaan Worldwall dalam Meningkatkan Minat Peserta Didik pada Materi Pembagian - Khansa Mehira Nisrina; Fi Jannatin Aliyah; Kowiyah Kowiyah (International Forum of Researchers and Lecturers, 2024)
Students often perceive math as a difficult subject, especially in primary school, even though it is a basic subject in everyday life and the advancement of science. Low learning outcomes result from this viewpoint as it undermines students' motivation and interest in learning math. This research looks at how the use of cutting-edge learning resources, such as Worldwall, can help students to understand and be more engaged in math, especially when it comes to division. The use of media can improve students' motivation, engagement and learning outcomes while helping them to overcome challenges related to understanding complex mathematical ideas. This research suggests that teachers use online learning tools such as Worldwall to make math lessons more interesting and dynamic.